Improving learning effectiveness for international construction joint ventures - Zhang, Liting (2009)
This Research is conducted within the context of international construction joint ventures (ICJVs). As unprecedented and massive economic development all over the world has been accompanied by an enormous expansion of the global construction market, ICJVs have played an important role in the strong growth of the construction industry. However, they are facing a myriad of problems and difficulties that have constrained the performance of ICJV projects. Since learning is regarded as an increasing important source for enhancing the performance of joint ventures (JVs), this research investigates ways to improve the effectiveness of learning in ICJVs. It aims to develop a learning model for an ICJV in order to identify the determinants of learning and assess their impact on learning effectiveness. To realize this, this study addresses two research questions, namely “What factors are conducive to learning effectiveness in ICJVs” and “How do these factors contribute towards learning effectiveness in ICJVs?”